Peningkatan Tingkat Kepuasan Dosen Terhadap Kualitas Pelayanan Pelatihan Jurnal Berkualitas Melalui Metode Servqual - Adhy Purnama; Ilah Sailah (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This study aims to provide information on the level of satisfaction of traineesJournal service quality training quality and the most influential factor in the region Ko3fgpertis III. Methods of data collection in this study using the registration documentation(questionnaires), interviews and observations. Data were analyzed using descriptiveanalysis techniques servqual quantitative analysis method and Cartesian diagrams usingSPSS 17. Based on the research results can be obtained gap (the gap value) of tangibledimension, realibility, responsivness, empathy, and assurance sequentially ie-1.69,-2.12,-2:09,-2.04, and-1.75. Based on the analysis Cartesian diagram attributes into three mainpriorities for repair iefriendliness, attention and courtesy of the staff committee and theirinstructors, clear information about the facility and rules for participants, classroomfacilities to support teaching and learning activities.